Ethical Values of Democracy According to John Dewey - Mulyatno, Carolus Borromeus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2014)
John Dewey never publishes a special work on theory of democracy. Nevertheless, his concern with democracy is undoubted. What is his main thought of democracy? This article is a textual analysis of the idea of democracy spread on his various works. As an experimentalist, his thought on democracy is to respond social problems. He views that two fundamental problems of democracy in his era are a tendency of reducing the meaning of democracy and social movements using violence in the name of political democracy. Dewey does not only look for the solution of the problems of democracy, but also put democracy in living process. The idea of liberty, equality and fraternity, as the democratic trinity, is ethical ideal of humanity. As an ethical idea, it should inspire each person in developing society for a better life. For this reason, he underlines the important of actualizing democracy through education.